Pengelolaan Antara Profesionalisme Guru dan Pengelolaan Pembelajaran di Kelas - Fina Safitri Nasution; Nadia Sabrina Siregar; Rifda Ramadina; Farhana Farhana; Hafiz Yusuf; Muhammad Rizki Maulana (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the current era of technology, almost all human activities require the help of sophisticated devices that can easily assist their activities. This certainly implies to educators and prospective educators to be able to apply ways of learning by utilizing the latest technology. Rapid technological developments now require innovation and transformation in learning. One of these innovations is blended learning. According to Jeanne Lam (2014) stated that traditional learning has often been carried out in learning so that in the current century the use of internet technology has begun to emerge, e-learning has been effectively used in higher education, one of which is learning with blended learning. In this modern era, technology demands innovation to improve the quality of education, including the development of learning media. The role of learning media is very important to support a more varied learning process. Good use of media can help educators in optimizing the learning process, so that educators will have more time to pay attention to other educational aspects, such as helping students' learning difficulties, personality formation , motivate learning, and others. Multimedia is a multimedia display designed by designers so that the appearance fulfills the function of informing messages and has interactivity to its users. while multimedia interactivity includes (1) users are involved to interact with application programs; and (2) information application aims to enable users to get the desired information choices without having to devour everything.